2017
DOI: 10.1080/15513815.2017.1303860
|View full text |Cite
|
Sign up to set email alerts
|

Higher Level of Oxidative Stress Markers in Small for Gestational Age Newborns Delivered by Cesarean Section at Term

Abstract: Elevated MDA levels and decreased SOD activity in umbilical cord blood may show the possibility of insufficient protective mechanisms against increased oxidative stress in SGA neonates born by cesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…SOD and CAT are essential natural scavengers of superoxide radicals and hydrogen peroxide to prevent organisms from undergoing oxidative stress injury (36). MDA, the final product of lipid oxidation, is a common indicator of lipid peroxidation of the cellular membrane (37). The changes in these oxidative parameters in this study imply that H 2 O 2 successfully induced oxidative stress in nasal epithelial cells and that high PTEN expression further worsens the induced injury.…”
Section: Discussionmentioning
confidence: 66%
“…SOD and CAT are essential natural scavengers of superoxide radicals and hydrogen peroxide to prevent organisms from undergoing oxidative stress injury (36). MDA, the final product of lipid oxidation, is a common indicator of lipid peroxidation of the cellular membrane (37). The changes in these oxidative parameters in this study imply that H 2 O 2 successfully induced oxidative stress in nasal epithelial cells and that high PTEN expression further worsens the induced injury.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, OSM (MDA, SOD) were measured in SGA infants delivered by cesarean section (n = 21) or vaginally (n = 21). Results showed that SGA term newborns delivered by caesarean section had insufficient protective mechanisms against increased OSM at birth [133].…”
Section: Osm (8-isoprostane; Malondialdehyde [Mda]; Protein Carbonyl mentioning
confidence: 97%
“…In humans, intrauterine growth restriction and a low birth weight is linked to increased oxidative stress, neuro-inflammation, perinatal mortality and lasting deficits in learning and memory in children and adolescents [242][243][244][245][246][247]. In addition, low vitC during pregnancy is linked to increased preterm births, pre-eclampsia and increased placental apoptosis; however, reports of a beneficial effect of antioxidant supplementation on these outcomes are currently conflicting [239,[248][249][250][251][252][253].…”
Section: Clinical Studiesmentioning
confidence: 99%